Risco ocupacional da infecção pelo vírus da hepatite B em centro obstétrico de hospital público de Porto Velho, Rondônia - SANTANA, Elaine Maria de (Universidade Federal do Pará, 2013)
The prevalence of HBsAg and anti-HBc was described in 168 individuals, distributed in 3 groups: 88 in-patients of the obstetric service, 61 health professionals of the obstetric center (PA CO) and 19 administrative employees (control group), all working at the Hospital de Base Dr. Ary Pinheiro - in Porto Velho, capital o fthe state of Rondônia. In the period of November and December of 2000 and January of 2001 serum samples were collected, for HBV detection using an enzyme immunoenzymatic assay (ELISA). The prevalence of the HBsAg was 1,1% of the obstetric patients, 3,3% in PAS/CO and 52,6% in the control group. For anti-HBc the positive results were 5,3% in the control group, 27,3% in the patient's group and 42,6% in the PAS/CO group. The study by age groups related to the positive serology, demonstrated that from 15 to 25 years and 25 to 35 years the prevalence of HBV was larger, for the patients and control, and in the groups of PAS/CO the higher prevalence was from 45 to 55 years. The high prevalence of HBV in the patient's way lead to a high prevalence of vertical transmission. The positive numbers of 1he control group is in agreement with the endemic characteristic of the population of Porto Velho. Factors as the number of sexual partners, the use of preservatives and the level of education in the PAS/CO group were compared with serological results for HBV. The organic fluid and the most referred exposure via of contamination or PAS/CO were the blood and cutaneous, 43% and 22% respectively.